2021
DOI: 10.21497/sefad.1031689
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Eğitimi Doktora Tezlerine Bütünsel Bir Yaklaşım (1995-2020)

Abstract: Bu çalışmada Türkiye'de 1995-2020 yılları arasında savunulan Türkçe Eğitimi doktora tezlerinin araştırma profilinin ortaya konması amaçlanmıştır. Araştırma, Yükseköğretim Kurulu Tez Merkezi verilerine dayalı olarak gerçekleştirilmiştir. Araştırmanın kapsamını Türkçe Eğitimi alanında tamamlanan toplam 248 doktora tezi oluşturmaktadır. Doktora tezleri yıllık tez üretimi, danışman unvanı, konu alanı, araştırma yöntem ve deseni, tezyayın oranı ölçütleri çerçevesinde ele alınmıştır. Çalışmanın verileri, içerik anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…The obligation to produce publications from graduate theses in associate professorship applications introduced by the Turkish Interuniversity Board and the obligation to publish before the thesis defense in some universities may be considered influential in the conversion of doctoral theses into publications. However, as Karagöz & Şeref (2021) point out, the production of publications from doctoral dissertations should not be seen solely as a means of meeting the criteria for promotion, and it is also important for young researchers to gain recognition and visibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obligation to produce publications from graduate theses in associate professorship applications introduced by the Turkish Interuniversity Board and the obligation to publish before the thesis defense in some universities may be considered influential in the conversion of doctoral theses into publications. However, as Karagöz & Şeref (2021) point out, the production of publications from doctoral dissertations should not be seen solely as a means of meeting the criteria for promotion, and it is also important for young researchers to gain recognition and visibility.…”
Section: Discussionmentioning
confidence: 99%
“…Another striking result of the research is that while the number of articles published in journals indexed in the field indexes is 8, no articles were published in journals indexed in SSCI, SCI, SCI-Expanded and AHCI indexes. Karagöz & Şeref (2021) analyzed doctoral dissertations completed between 1995 and 2020 in Turkish language teaching and concluded that the publications produced from thesis were mostly published as national articles in journals originating from Turkey and that the number of publications listed in the Web of Science (SSCI/ESCI/AHCI) citation index was quite low. Therefore, it is suggested that the quality of doctoral dissertations in the field of TTFL should be reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışma sonucunda anlama becerisine yönelik doktora tezlerinde daha çok profesör doktor unvanlı öğretim üyelerinin danışmanlık yaptığı anlaşılmıştır. Bu sonuç, alan yazındaki diğer çalışmalarla (Boyacı ve Demirkol, 2018;Karagöz ve Şeref, 2021) örtüşmektedir. Lisansüstü Eğitim ve Öğretim Yönetmeliğine göre doktora programında bir öğrencinin danışmanlığını yürütebilmek için en az bir yüksek lisans öğrencisini mezun etmek gerekmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…A vast number of analysis studies providing a general overview of publications in the field of Turkish language teaching have been carried out (Sevim & İşcan, 2012;Coşkun, Özçakmak, & Balcı, 2012;Varışoğlu, Şahin, & Göktaş, 2013;Yağmur Şahin, Kana, & Varışoğlu, 2013;Aktaş & Yurt, 2015;Özçakmak, 2017;Boyacı & Demirkol, 2018;Önal & Maden, 2021;Karagöz & Şeref, 2021;Demir, 2021;Demir & Çalışkan, 2021). Upon examining these studies, it becomes evident that many of them have focused on analyzing postgraduate studies, while several studies have examined master's theses and doctoral dissertations together or separately.…”
Section: Introductionmentioning
confidence: 99%